High Genetic Diversity and Rickettsia felis in Pediculus humanus Lice Infesting Mbuti (pygmy people), -Democratic Republic of Congo - Amanzougaghene, Nadia; Drali, Rezak; Shako, Jean-Christophe; Davoust, Bernard; Fenollar, Florence; Raoult, Didier; Mediannikov, Oleg (Frontiers in Cellular and Infection Microbiology, 2022)
Pediculus humanus is an obligate bloodsucking parasite of humans that has two ecotypes, the head louse and the body louse, which share an intimate history of coevolution with their human host. In the present work, we obtained and analysed head and body lice collected from Mbuti pygmies living in the Orientale province of the Democratic Republic of the Congo. Cytochrome b DNA analysis was performed in order to type the six known lice clades (A, D, B, F, C and E). The results revealed the presence of two mitochondrial clades. Clade D was the most frequent (61.7% of 47), followed by clade A (38.3% of 47). Sixteen haplotypes were found in 47 samples, of which thirteen were novel haplotypes, indicating an unusually high genetic diversity that closely mirrors the diversity of their hosts. Moreover, we report for the first time the presence of the DNA of R. felis in three (6.4% of 47) head and body lice belonging to both clades A and D. Additional studies are needed to clarify whether the Pediculus lice can indeed transmit this emerging zoonotic bacterium to their human hosts.